2003
DOI: 10.1590/s1415-52732003000200008
|View full text |Cite
|
Sign up to set email alerts
|

Adições crescentes de ácido fítico à dieta não interferiram na digestibilidade da caseína e no ganho de peso em ratos

Abstract: O crescente consumo de alimentos de origem vegetal, sejam como fontes protéicas com baixo teor de gordura ou como fontes de fibras, tem acrescido à dieta humana o ácido fítico. Devido à sua carga altamente negativa, o ácido fítico tem sido visto como componente de ação antinutricional capaz de quelar minerais bivalentes, proteínas e amido, podendo comprometer a biodisponibilidade destes nutrientes. No presente estudo investigou-se a influência da adição de ácido fítico à dieta de caseína, em concentrações igua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
1
1
1
7
Order By: Relevance
“…This image analysis algorithm provides a robust and flexible method for objective immunohistochemical analysis of samples stained with up to three different stains using a laboratory microscope, standard RGB camera setup and the public domain program NIH Image 16 . The absence of significant differences in weight gain across groups (p = 0.2274) corroborates results from other studies where no weight changes were observed when IP6 was supplied 17 even when the dietary and proteic quality of the animal chow was evaluated. In the present study, food was supplied ad libitum, since a calorie-restricted diet has been shown elsewhere to decrease significantly the expression of the proteins TGF-beta1/ beta2 and COX-2 in the mucosa of obese rats 18 .…”
Section: Discussionsupporting
confidence: 88%
“…This image analysis algorithm provides a robust and flexible method for objective immunohistochemical analysis of samples stained with up to three different stains using a laboratory microscope, standard RGB camera setup and the public domain program NIH Image 16 . The absence of significant differences in weight gain across groups (p = 0.2274) corroborates results from other studies where no weight changes were observed when IP6 was supplied 17 even when the dietary and proteic quality of the animal chow was evaluated. In the present study, food was supplied ad libitum, since a calorie-restricted diet has been shown elsewhere to decrease significantly the expression of the proteins TGF-beta1/ beta2 and COX-2 in the mucosa of obese rats 18 .…”
Section: Discussionsupporting
confidence: 88%
“…Oliveira et al (2003) encontraram 14,7 mg de ácido fítico por grama de feijão cru. Os dados são superiores aos encontrados na Tabela 1.…”
Section: Resultsunclassified
“…onde y = leitura da absorbância a 605 nm; e x = concentração de cianeto total(µgHCN.mL -1 ) diminuem sua digestibilidade (OLIVEIRA et al, 2003;OLIVEIRA et al, 2001). …”
Section: Avaliação Toxicológica Das Inflorescências De Gengibreunclassified